Dynamics of positive changes in physical training of students under the influence of independent classes - Nazarenko, I. (Problems of Engineer-Pedagogical Education, 2021)
This article examines and analyzes the latest current research on the organization and teaching of the subject "Physical Education" at higher education institutions. The reasons and problems of contemporary students’ health and physical fitness deterioration as well as the reasons for their lack of motivation to get physically educated, exercise and do sports are considered. Today, the system of physical education at higher education institutions is undergoing a complex process of reform. There is a low level of physical fitness among modern youth due to insufficient physical activity. The analysis of scientific and methodological literature shows a lack of information on the level of physical fitness of students and its dynamics in recent years. The paper highlights the need to conduct educational work among student youth and instill in them a love of a healthy lifestyle, increase interest and habits in independent physical culture and sports in everyday life. The article examines the current state of physical fitness of students, analyzes previous studies on this issue and reveals that the amount of physical activity of students and modern youth in general is steadily decreasing, along with their interest and motivation to exercise and do sports. This has a negative impact on the physical development, physical fitness and functional state of young people. The results of comparative analysis of indicators of physical fitness of students of Ukrainian Engineering and Pedagogical Academy are given and allow stating that there is a decrease in the level of physical fitness. The problems of deteriorating health and physical fitness of students, which are the result of unconscious attitude to their health, healthy lifestyle, work and leisure, are considered. Students' self-exercise and their conscious attitude to their own health should become one of the most important components of the educational process. With sufficient practical knowledge and skills in physical education, they will be able to maintain and strengthen their physical and mental health in professional activities and daily life. Given the realities of today, when students are forced to spend all their time being involved in mental activity, it is important to pay attention to maintaining and improving their health.